The Correlation between Family Care with Character Development of Early Childhood - Darminto Darminto; Ismaniar Ismaniar (Universitas Negeri Padang, 2019)
This research is motivated by the low level of family care with the development of the character of early childhood in ther RW. V Kelurahan Indarung Kecamatan Lubuk Kilangan Padang City. The objectives of the study describe this include: (1) family care, (2) character development, and (3) the relationship of family care with the development of the character of children at RW. V Kelurahan Indarung Kecamatan Lubuk Kilangan Padang City. This study included quantitative research with correlational types. Population in this study were parents of early childhood totaling 30 people, samples were taken by 25 people from a population of 30 people with a sampling technique that was random sampling. Data collection techniques use questionnaires, and data collection tools using questionnaires. Data collection techniques are questionnaires, while data collection tools use questionnaires or statement lists. The results of the study show that: (1) the relationship of family care to early childhood is in the very low category, (2) the relationship between the development of the character of early childhood is in the low category, and (3) there is a relationship between family care and the development of the character of the children.Keywords: Family Care, Character Development, Early Childhood